Peramalan Tonase Sampah TPST Bantargebang Sebagai Upaya Awal Penanganan Masalah Sampah Daerah Khusus Jakarta - Zedha, Hazulil Fitriah; Anwar, Samsul; AR, Fitriana (Jurnal Kesehatan Lingkungan Indonesia, 2025)
Latar belakang: Salah satu masalah lingkungan yang timbul akibat semakin bertambahnya jumlah penduduk yang disertai dengan perubahan pola hidup di Daerah Khusus Jakarta (DKJ) adalah pengelolaan sampah yang semakin kompleks dengan kuantitas yang mencapai 7.000 ton/harinya. Penelitian ini bertujuan untuk meramalkan tonase sampah yang mungkin dihasilkan pada masa yang akan datang sebagai salah satu upaya awal dalam membantu proses penyusunan rencana pengelolaan sampah yang lebih baik.Metode: Penelitian ini menganalisis data tonase sampah bulanan yang masuk ke TPST Bantargebang yang diperoleh dari website Jakarta Open Data. Data dianalisis dengan menggunakan statistika deskriptif dan inferensia dengan menggunakan metode Triple Exponential Smoothing (TES) dan Autoregressive Fractionally Integrated Moving Average (ARFIMA).Hasil: Peramalan dengan metode terbaik menunjukkan bahwa tonase sampah yang masuk ke TPST Batargebang diprediksi akan semakin tinggi setiap tahunnya terutama pada bulan Desember dan Januari. Tonase sampah pada bulan Desember tahun 2026 diprediksi mencapai 293.317,5 ton, jauh meningkat dari hasil prediksi pada bulan Desember tahun 2021 yang hanya mencapai 254.113,3 ton. Simpulan: Hasil peramalan tonase sampah pada penelitian ini dapat menjadi salah satu acuan dalam upaya penanganan sampah di DKJ. Pemerintah DKJ bersama seluruh komponen masyarakat perlu bekerjasama dalam mengantisipasi lonjakan sampah tersebut dengan melakukan berbagai upaya yang dapat menekan laju peningkatan tonase sampah di Jakarta dan sekitarnya. Pemerintah DKJ direkomendasikan untuk memperbaiki sistem pengelolaan sampah, baik di tingkat masyarakat maupun di TPST Batargebang dengan mengeluarkan regulasi/aturan pengelolaan sampah yang lebih efektif, menambah anggaran pengelolaan sampah dan melakukan sosialisasi serta pembinaan terutama bagi masyarakat yang tinggal di wilayah padat penduduk. ABSTRACT Forecasting Waste Tonnage at TPST Bantargebang as an Initial Effort to Handle Waste Problems in Special Region of JakartaBackground: One of the environmental problems arising from the increasing population accompanied by changes in lifestyle in the Special Region of Jakarta (DKJ) is increasingly complex waste management with quantities reaching 7,000 tons per day. This study aims to forecast the tonnage of waste that may be generated in the future as one of the initial efforts in helping the process of preparing a better waste management plan .Method: This study analyzes monthly waste tonnage data entering TPST Bantargebang obtained from the Jakarta Open Data website. The data was analyzed using descriptive and inferential statistics using the Triple Exponential Smoothing (TES) and Autoregressive Fractionally Integrated Moving Average (ARFIMA) methods..Result: Forecasting with the best method shows that the tonnage of waste entering TPST Batargebang is predicted to be higher every year, especially in December and January. The waste tonnage in December 2026 is predicted to reach 293,317.5 tons, a far increase from the prediction results in December 2021 which only reached 254,113.3 tons. Conclusion: The results of forecasting the tonnage of waste in this study can be one of the references in waste management efforts in DKJ. The DKJ government together with all components of society need to work together in anticipating the surge in waste by making various efforts that can reduce the rate of increase in waste tonnage in Jakarta and its surroundings. The DKJ government is recommended to improve the waste management system, both at the community level and at TPST Batargebang by issuing more effective waste management regulations, increasing the waste management budget and conducting socialization and guidance, especially for people living in densely populated areas. ABSTRACT Forecasting Waste Tonnage at TPST Bantargebang as an Initial Effort to Handle Waste Problems in Special Region of JakartaBackground: One of the environmental problems arising from the increasing population accompanied by changes in lifestyle in the Special Region of Jakarta (DKJ) is increasingly complex waste management with quantities reaching 6,500 to 7,000 tons per day. This study aims to forecast the tonnage of waste that may be generated in the future as one of the initial efforts in helping the process of preparing a better waste management plan .Method: This study analyzes monthly waste tonnage data entering TPST Bantargebang obtained from the Jakarta Open Data website. The data was analyzed using descriptive and inferential statistics using the Triple Exponential Smoothing (TES) and Autoregressive Fractionally Integrated Moving Average (ARFIMA) methods..Result: Forecasting with the best method shows that the tonnage of waste entering TPST Batargebang is predicted to be higher every year, especially in December and January. The waste tonnage in December 2026 is predicted to reach 293,317.5 tons, a far increase from the prediction results in the same month for 2021 which only reached 254,113.3 tons. Conclusion: The results of forecasting the tonnage of waste entering the TPST Batargebang in this study can be one of the references in waste management efforts in DKJ. The DKJ government together with all components of society need to work together in anticipating the surge in waste by making various efforts that can reduce the rate of increase in waste tonnage in Jakarta and its surroundings. The DKJ government is recommended to improve the waste management system, both at the community level and at TPST Batargebang by issuing more effective waste management regulations, increasing the waste management budget and conducting socialization and guidance, especially for people living in densely populated areas.